Moodle as a Tool to Reduce Transactional Distance at an Open Distance and e-Learning University - Kershnee Sevnarayan (Studies in Learning and Teaching, 2023)
Despite the expansion of e-learning and the adoption of innovative learning management systems to support students, higher education institutions are still struggling under the burden of digital exclusion, hence increasing the transactional distance between lecturers and students. The research was conducted at a South African Open Distance and eLearning university and attempted to (1) understand how the Moodle site is organized to influence transaction distance, (2) identify students’ perceptions of the Moodle site to enhance their academic writing skills, and (3) identify if Moodle is an enabler or disabler to their learning. This article uses a qualitative participatory action research design and draws on the theory of transactional distance. Using observations, open-ended evaluation questions, and a focus group discussion, the study found that students appreciated the communication and interaction facilitated by the lecturers. Despite the challenges that students experienced, the transactional distance was reduced between lecturers and students. Although the findings of this study cannot be generalized on a broader scale, findings are in line with similar studies, amplifying the critical role of the perceptions and challenges of first-year students in HEIs to bring about the required change.